Rhinopharyngitis and ENT morbidity among cement workers with long-term occupational exposure in Kongo Central Province, DRC - Marie Ditu Kula; Jean Paul Pholo Manzimbala; Papy Steve Mbelambela Etongola; Lema Gabriel; Gibency Mfulani Mpenda; Eddy Mbambu Mampuya; Christian Matanda Nzanza; Marie Catherine Mbutshu Okitambolo; Allen Kondi Makani; Richard Matanda Nzanza; Jerome Sokolo Gedikondele (Orapuh Journal)
Introduction